Pengaruh Gaya Kepemimpinan, Disiplin, Dan Motivasi Kerja Terhadap Kinerja Pegawai Pusat Pengembangan Perpustakaan Umum Dan Khusus Pada Perpustakaan Nasional Republik Indonesia - Funtayah, Desty Ayatun; Hendrarso, Panji (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The aim of this research is to find out and analyze how much leadership style, work discipline and motivation influence the performance of PPPUK National Library employees. The research method is quantitative research using survey methods with correlational analysis techniques. In this study, the sample used was 51 PPPUK employees. Data was processed using SPSS 25 with the f test, t test, multiple linear regression, and coefficient of determination. The results of the research show that there is a partially significant influence between leadership style on employee performance in partial test (t test) t count 4,806 > 2,011 with a significance value of 0.004 < 0.05. There is a partially significant influence between discipline on employee performance in the partial test (t test) t count 4.728 > 2.011 with a significance value of 0.004 < 0.05. There is a partially significant influence between motivation on employee performance in the partial test (t test) t count 5.060 > 2.011 with a significance value of 0.001 < 0.05. Then there is the influence of leadership style, work discipline and motivation on employee performance with an F test result of 1.543 > 0.235, coefficient of determination (R_Square) of 0.90. This shows that the magnitude of the influence of leadership style, discipline and motivation variables on employee performance is 90%, while the remaining 10% is influenced by other factors not included in this research.